A kinetic degradation study of curcumin in its free form and loaded in polymeric micelles - Naksuriya O. (2017)
© 2015 American Association of Pharmaceutical Scientists. Curcumin, a phenolic compound, possesses many pharmacological activities and is under clinical evaluation to treat different diseases. However, conflicting data about its stability have been reported. In this study, the kinetic degradation of curcumin from a natural curcuminoid mixture under various conditions (pH, temperature, and dielectric constant of the medium) was investigated. Moreover, the degradation of pure curcumin at some selected conditions was also determined. To fully solubilize curcumin and to prevent precipitation of curcumin that occurs when low concentrations of co-solvent are present, a 50:50 (v/v) aqueous buffer/methanol mixture was used as standard medium to study its degradation kinetics. The results showed that degradation of curcumin both as pure compound and present in the curcuminoid mixture followed first order kinetic reaction. It was further shown that an increasing pH, temperature, and dielectric constant of the medium resulted in an increase in the degradation rate. Curcumin showed rapid degradation due to autoxidation in aqueous buffer pH=8.0 with a rate constant of 280×10 -3 h -1 , corresponding with a half-life (t 1/2 ) of 2.5 h. Dioxygenated bicyclopentadione was identified as the final degradation product. Importantly, curcumin loaded as curcuminoid mixture in ω-methoxy poly (ethylene glycol)-b-(N-(2-benzoyloxypropyl) methacrylamide) (mPEG-HPMA-Bz) polymeric micelles and in Triton X-100 micelles was about 300-500 times more stable than in aqueous buffer. Therefore, loading of curcumin into polymeric micelles is a promising approach to stabilize this compound and develop formulations suitable for further pharmaceutical and clinical studies.